2006
DOI: 10.1074/jbc.m606409200
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CNGB1 Protein Leads to Olfactory Dysfunction and Subciliary Cyclic Nucleotide-gated Channel Trapping

Abstract: Olfactory receptor neurons (ORNs) employ a cyclic nucleotide-gated (CNG) channel to generate a receptor current in response to an odorant-induced rise in cAMP. This channel contains three types of subunits, the principal CNGA2 subunit and two modulatory subunits (CNGA4 and CNGB1b). Here, we have analyzed the functional relevance of CNGB1 for olfaction by gene targeting in mice. Electro-olfactogram responses of CNGB1-deficient (CNGB1 ؊/؊ ) mice displayed a reduced maximal amplitude and decelerated onset and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 50 publications
6
71
0
Order By: Relevance
“…This also correlates with a critical role for the β-subunit in transport of the channel complex to the plasma membrane. Indeed, it has been demonstrated that the olfactory β-subunit (an alternatively spliced product of the Cngb1 locus) is required for ciliary transport of the olfactory cAMPgated cation channel (Jenkins et al, 2006;Michalakis et al, 2006). Our observed reduction of GC1 and ABCA4 may similarly reflect a broader role for the photoreceptor β-subunit in transport of select proteins to ROS.…”
Section: Journal Of Cell Science 122 (8)mentioning
confidence: 60%
“…This also correlates with a critical role for the β-subunit in transport of the channel complex to the plasma membrane. Indeed, it has been demonstrated that the olfactory β-subunit (an alternatively spliced product of the Cngb1 locus) is required for ciliary transport of the olfactory cAMPgated cation channel (Jenkins et al, 2006;Michalakis et al, 2006). Our observed reduction of GC1 and ABCA4 may similarly reflect a broader role for the photoreceptor β-subunit in transport of select proteins to ROS.…”
Section: Journal Of Cell Science 122 (8)mentioning
confidence: 60%
“…Coronal cryosections (10 m) were thaw-mounted onto glass slides (Polysciences) and incubated for 1 h in blocking solution (4% horse serum, 0.3% Triton X-100 in PBS), followed by incubation in primary antibody prepared in blocking solution. For CNGA3 labeling we used a rabbit primary antiserum at 1:1000 (Michalakis et al, 2006). Nav1.8 labeling used a rabbit polyclonal serum (Sigma, 1:100 dilution) directed against the peptide CEDEVAAKEGNSPGPQ.…”
Section: Methodsmentioning
confidence: 99%
“…Locomotor activity was measured in an infrared beam operated open field ActiMot/MoTil system (25!25 !25 cm, ActiMot System, Midland, MI, USA; Michalakis et al 2006). Horizontal motor activity was evaluated by monitoring the beam breaks in the X and Y coordinates of the animal and thus its location for 24 h.…”
Section: Locomotor Activitymentioning
confidence: 99%